PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA ISLAMIC BOARDING SCHOOL TINGKAT SMA DI YOGYAKARTA - Arief Darmawan; Maisaroh Maisaroh (Jurnal Aplikasi Bisnis, 2018)
This research examine the influence of transformational leadership and job satisfaction on organizational citizenship behavior, relationship between variables and how transformational leadership and organizational citizenship behavior are applicated to the school at Islamic boarding high school in Yogyakarta. This research examine four hypothesis, it were there is positive influence between variable of transformational leadership toward organizational citizenship behavior; there is positive influence between job satisfaction variable with organizational citizenship behavior; there is positive influence between variable of transformational leadership and job satisfaction; between transformational leadership variable to organizational citizenship behavior with intervening variable of job satisfaction. Using SPSS 17, analyzing data through several stages of analysis, first, requirements analysis test, path coefficient test, and significance test of path coefficient analysis. The result of path analysis shows that simultaneously independent variables of transformational leadership and job satisfaction have influence on the organization citizenship behavior (f-value 23.455 with a significance level of 0.00).